Relationship between foreign language anxiety, listening anxiety, self-efficacy, and listening comprehension performance of Iranian EFL learners - Serraj, Samaneh (2014)
Anxiety and self- efficacy are affective factors that have influential impact on foreign language learning domains and play crucial role in language learners’ performance. In the Iranian EFL context listening comprehension remains as one of the most problematic skills for EFL learners to obtain and for instructors to instruct. The present study is an attempt to investigate the effect of Iranian EFL learners’ listening comprehension anxiety, foreign language anxiety and listening self-efficacy on their listening comprehension performance. Furthermore, the study seeks to identify the factors that cause and reduce listening anxiety. Moreover, the possible relationship between foreign language anxiety, listening anxiety and listening self-efficacy is sought. Lastly, the study seeks to determine the extent to which the level of anxiety varies at different levels of proficiency. The study adopts a primarily quantitative approach, followed by qualitative data aimed at expanding and elaborating on the quantitative data. Two hundred and ten EFL learners in two levels of intermediate and advanced took part in the study. A packet of questionnaires was employed to measure listening comprehension anxiety, language learning anxiety and language listening self-efficacy. To figure out learners’ sources of listening comprehension anxiety and the factors that might reduce listening anxiety, the semi-structured interviews were conducted with seven participants in order to arrive at richer findings. Further, all participants took part in listening tests in order to find out if their listening comprehension anxiety, foreign language anxiety and listening selfefficacy are related to their listening comprehension performance. Results showed that learners in both groups experience listening anxiety and it is the best predictor of learners’ listening comprehension performance among other variables. Moreover, it was found that listening anxiety and foreign language anxiety are negatively correlated with learners’ listening comprehension while listening selfefficacy is positively correlated with learners’ listening comprehension. Furthermore,result showed that the level of FL anxiety, listening anxiety and listening self-efficacy do not differ across two levels of proficiency. The factors that were identified as having influence on listening anxiety were divided into three categories, i.e. individual factors (nerves and emotionality, using inappropriate strategies and lack of practice), input factors (lack of time to process, lack of visual support, nature of speech and level of difficulty) and environmental factors (instructors, peers and class environment). Moreover, connectedness, instructors and type of listening materials were identified as factors that reduce listening anxiety among Iranian language learners. Based on the findings of the study, a foreign language listening anxiety model of factors influencing Iranian learners’ listening comprehension is proposed. The findings of the study draw the attention of EFL instructors to encourage their learners seek approaches to reduce their listening anxiety. Pedagogical implications for language teachers and learners are provided as well.